EFEKTIVITAS STUDI BANDING JAGUNG, TINGKAT PARTISIPASI DAN TINGKAT PENERAPAN PADA PETANI DI KABUPATEN KULON PROGO (CORN COMPARISON STUDY EFFECTIVENESS, LEVEL OF PARTICIPATION AND LEVEL OF IMPLEMENTATION BY FARMERS IN KULON PROGO DISTRICT) - Sujono, Sujono (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2010)
The research was aimed to: 1) identify the effectiveness of corn comparison study towards farmers attitude, knowledge, skill and motivation; 2) identify farmers level of participation in farmer group activities after the comparison study; 3) identify the effictiveness of attitude, knowledge, skill, motivation and participation towards the implementation of the comparison study material by farmers. The research was performed in Kulon Progo, Yogtakarta during November 2009 - February 2010, using survey methods combining quantitative and qualitative approaches. Corn comparison study bring negative impact on farmer group participation (planning, expense, implementation and norms obedience). Farmers participation level in farmer group activities after participating is in the form of knowledge and attitude changes, while skill and motivation do not affect participation. Material implementation level by farmers are affected by knowledge, attitude, skill, but motivation and participation remain unchanged.